From deglaciation to the Early Holocene in the northern Appalachians: A multiproxy palaeoenvironmental record from Scotstown Bog, Québec, Canada - Leeli Amon; Jeannine‐Marie St‐Jacques; Ekaterina Ershova; Kathryn E. Hargan; Charlotte Mary Cotter Whyte; Dirk Sachse; Oliver Rach; Matthew C. Peros (Journal of Quaternary Science, 2025)
A multiproxy study of a sediment sequence from a Québec peatbog characterises the rapid and significant environmental responses to changing climatic conditions from the deglaciation of the Laurentide Ice Sheet to the early Holocene period. Scotstown Bog (45°30'45.0“N, 71°11'42.0“W) is an ombrotrophic peatland on the edge of the Appalachian Uplands in southern Québec, Canada. We reconstructed its Late‐glacial and early Holocene palaeoenvironments for 14 000–6 000 cal a bp using palaeobotanical (plant macrofossil, macrocharcoal, pollen analyses), faunal (chironomid analysis), sedimentological (grain‐size analysis, sediment organic content), and geochemical (sedimentary n ‐alkanes and hydrogen isotope analyses) methods. We targeted our multiproxy reconstruction on the Late‐glacial period, which provides an example of how biota can respond to profound changes in climatic and environmental conditions. A major transition occurred between 13 000 and 12 900 cal a bp , which is recorded in all palaeoecological proxies. Our reconstruction reveals two major environmental changes at this time. First, the Scotstown basin became isolated from a larger proglacial lake, as shown by sedimentological changes, sediment grain size and chironomid assemblage shift. Second, plant macrofossils and pollen influx show contemporaneous major shifts in the vegetation composition from tundra to tree‐line to closed‐canopy forested communities.

The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ensuring climate services serve society: examining tribes’ collaborations with climate scientists using a capability approach - Scott E. Kalafatis; Kyle Powys Whyte; Julie C. Libarkin; Chris Caldwell (Climatic Change, 2019)

Current knowledge and breeding perspectives for the spider plant (Cleome gynandra L.): a potential for enhanced breeding of the plant in Africa - A. O. Kwarteng; J. Abogoom; R. Adu Amoah; D. Nyadanu; T. Ghunney; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; D. D. Asiedu; T. Whyte (Genetic Resources and Crop Evolution, 2018)

Current knowledge and breeding avenues to improve upon Frafra potato (Solenostemon rotundifolius (Poir.) J. K. Morton) - A. O. Kwarteng; T. Ghunney; R. Adu Amoah; D. Nyadanu; J. Abogoom; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; T. Whyte; D. D. Asiedu (Genetic Resources and Crop Evolution, 2018)

Microscopic characterization of the bacterial cell envelope of Planococcus halocryophilus Or1 during subzero growth at −15 °C - N. C. S. Mykytczuk; J. R. Lawrence; C. R. Omelon; G. Southam; L. G. Whyte (Polar Biology, 2016)

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)

A fixed‐dose approach to conducting emamectin benzoate tolerance assessments on field‐collected sea lice, Lepeophtheirus salmonis - S K Whyte; J D Westcott; A Elmoslemany; K L Hammell; C W Revie (Journal of Fish Diseases, 2013)
In N ew B runswick, C anada, the sea louse, L epeophtheirus salmonis, poses an on‐going management challenge to the health and productivity of commercially cultured A tlantic salmon, S almo salar . While the in‐feed medication, emamectin benzoate ( SLICE ® ; M erck), has been highly effective for many years, evidence of increased tolerance has been observed in the field since late 2008. Although bioassays on motile stages are a common tool to monitor sea lice sensitivity to emamectin benzoate in field‐collected sea lice, they require the collection of large numbers of sea lice due to inherent natural variability in the gender and stage response to chemotherapeutants. In addition, sensitive instruments such as EC 50 analysis may be unnecessarily complex to characterize susceptibility subsequent to a significant observed decline in efficacy. This study proposes an adaptation of the traditional, dose–response format bioassay to a fixed‐dose method. Analysis of 657 bioassays on preadult and adult stages of sea lice over the period 2008–2011 indicated a population of sea lice in N ew B runswick with varying degrees of susceptibility to emamectin benzoate. A seasonal and spatial effect was observed in the robustness of genders and stages of sea lice, which suggest that mixing different genders and stages of lice within a single bioassay may result in pertinent information being overlooked. Poor survival of adult female lice in bioassays, particularly during M ay/ J une, indicates it may be prudent to consider excluding this stage from bioassays conducted at certain times of the year. This work demonstrates that fixed‐dose bioassays can be a valuable technique in detecting reduced sensitivity in sea lice populations with varying degrees of susceptibility to emamectin benzoate treatments.

Sea lice monitoring on A tlantic salmon farms in N ew B runswick, C anada: comparing audit and farm staff counts - A Elmoslemany; S K Whyte; C W Revie; K L Hammell (Journal of Fish Diseases, 2013)
Sea lice audits were performed by the A tlantic V eterinary C ollege on commercial aquaculture sites in N ew B runswick, C anada, in 2011. Although the primary objective was to verify that farms were reporting similar lice counts to third‐party counts, more detailed comparisons were made to identify when lice counts were more likely to differ between the audit team and farm employees. A total of 28 sea lice audits were conducted on 16 sites between J une and D ecember 2011. During each audit, 10 cages were evaluated per site where possible, with ten fish per cage being evaluated by an audit technician and a further ten by a farm employee. Data analysis included descriptive statistics of lice counts by stage and limits of agreement plots. A random effects negative binomial model that accounted for clustering of cages within sites was applied to assess the effect of counter type and season on lice counts by stage. The results indicate that farms counts were generally in agreement with audit counts. However, when the average counts for chalimus and preadult (male and female) and adult male lice stages were high, farm counters were more likely to report a lower value. Higher lice counts were observed during autumn compared to summer especially for the adult female stage. Finally, there was a significant clustering effect for site and cage, with most of the variation attributable to site.

Microbial diversity and activity in hypersaline high Arctic spring channels - Chih-Ying Lay; Nadia C. S. Mykytczuk; Thomas D. Niederberger; Christine Martineau; Charles W. Greer; Lyle G. Whyte (Extremophiles, 2012)

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

Cardiovascular function and the veteran athlete - M. Wilson; R. O’Hanlon; S. Basavarajaiah; K. George; D. Green; P. Ainslie; S. Sharma; S. Prasad; C. Murrell; D. Thijssen; A. Nevill; G. Whyte (European Journal of Applied Physiology, 2010)

Quantitative linkage genome scan for atopy in a large collection of Caucasian families - Bradley T. Webb; Edwin van den Oord; Anthony Akkari; Steve Wilton; Tina Ly; Rachael Duff; Kathleen C. Barnes; Karin Carlsen; Jorrit Gerritsen; Warren Lenney; Michael Silverman; Peter Sly; et al. (Human Genetics, 2007)

New sources of resistance to Radopholus similis in Musa germplasm from Asia - C. Dochez; J. Dusabe; J. Whyte; A. Tenkouano; R. Ortiz; D. De Waele (Australasian Plant Pathology, 2006)

The Effect of Creosote on Vitellogenin Production in Rainbow Trout (Oncorhynchus mykiss) - J. P. Sherry; J. J. Whyte; N. A. Karrow; A. Gamble; H. J. Boerman; N. C. Bol; D. G. Dixon; K. R. Solomon (Archives of Environmental Contamination and Toxicology, 2006)

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003 - O. M. Murphy; S. Murchan; D. Whyte; H. Humphreys; A. Rossney; P. Clarke; R. Cunney; C. Keane; L. E. Fenelon; D. O’Flanagan (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Effect of Maintaining Rainbow Trout in Creosote Microcosms on Lens Optical Properties and Liver 7-Ethoxyresorufin- O -Deethylase (EROD) Activity - J. J. Whyte; K. L. Herbert; N. A. Karrow; D. G. Dixon; J. G. Sivak; N. C. Bols (Archives of Environmental Contamination and Toxicology, 2000)

Growth activation of the microalga Isochrysis galbana by the aqueous extract of the seaweed Monostroma nitidum - Ji Young Cho; Hyung-Joo Jin; Hyun Jeong Lim; John N. C. Whyte; Yong-Ki Hong (Journal of Applied Phycology, 1998)